2006
DOI: 10.1016/j.ijdevneu.2006.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Intrastriatal hypoxanthine administration affects Na+,K+‐ATPase, acetylcholinesterase and catalase activities in striatum, hippocampus and cerebral cortex of rats

Abstract: The aim of this study was to investigate the effects of a single intrastriatal injection of hypoxanthine, the major metabolite accumulating in Lesch-Nyhan disease, on Na(+),K(+)-ATPase, acetylcholinesterase and catalase activities in striatum, cerebral cortex and hippocampus of rats at different post-infusion periods. Adult Wistar rats were divided in two groups: (1) vehicle-injected group (control) and (2) hypoxanthine-injected group. For Na(+),K(+)-ATPase activity determination, the animals were sacrificed 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Impaired energy metabolism may trigger proapoptotic signalling (programmed cell death), oxidative damage to lipids, protein and DNA, and impair mitochondrial DNA repair. 14,15 It has been demonstrated that alterations in energy metabolism seem to be implicated in the pathogenesis of a number of muscle and neurological complications, [16][17][18] metabolic disorders, [19][20][21][22] aging [23][24][25] and neuromuscular diseases. 26,27 Mitochondrial function and structure/integrity is crucial to maintaining the energy supply for optimal function and maintenance of homeostasis in some tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired energy metabolism may trigger proapoptotic signalling (programmed cell death), oxidative damage to lipids, protein and DNA, and impair mitochondrial DNA repair. 14,15 It has been demonstrated that alterations in energy metabolism seem to be implicated in the pathogenesis of a number of muscle and neurological complications, [16][17][18] metabolic disorders, [19][20][21][22] aging [23][24][25] and neuromuscular diseases. 26,27 Mitochondrial function and structure/integrity is crucial to maintaining the energy supply for optimal function and maintenance of homeostasis in some tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Impaired energy metabolism may trigger proapoptotic signalling (programmed cell death), oxidative damage to lipids, protein and DNA, and impair mitochondrial DNA repair . It has been demonstrated that alterations in energy metabolism seem to be implicated in the pathogenesis of a number of muscle and neurological complications, metabolic disorders, aging and neuromuscular diseases …”
Section: Introductionmentioning
confidence: 99%